Osteonecrosis of the jaw and the role of macrophages. - Pazianas, M (2011)
Nitrogen-containing bisphosphonates have been associated with the development of osteonecrosis of the jaws (ONJ), but the lack of reliable epidemiological data and appropriate animal models has restricted our understanding of ONJ pathophysiology and limited its management. The best available information is from histopathologic findings, which implicate bone necrosis and infection, although it is not clear which is primary. However, there are data suggesting that macrophages could well be the central factor in allowing the infection to develop first, followed by local necrosis, which could also account for the development of ONJ in patients treated with denosumab, a human monoclonal antibody to the receptor activator of nuclear factor-κB ligand. This review examines the evidence that macrophages could play a prominent role in development of ONJ and the proposal that it may be more appropriate to view ONJ as a drug and not only a bisphosphonate-related complication.